Expérience d’écriture créative, entre lecture critique du roman britannique contemporain et vieilles histoires de famille - Isabelle HERVOUET (E-REA)
Based on an experience of creative writing (the turning into a narrative of family history reconstructed by means of birth registers and other public records), this article shows how academic methodologies facilitated every stage of creative writing. More specifically, the critical reading of contemporary British literature made it possible to adequately problematize key issues and formulate responses to questions that arose during the writing process, and thus to transform the archive into a narrative for readers who, in this particular instance, were family members.This paper tracks the writing process, from the initial questions related to the retrieval of a “life”, in the biographical sense, from meagre archival data, to the type of text that can emerge from this type of research and to considering varied solutions to the problem of the integration of fiction into biography. Creative writing thus appears closely linked to the critical reading of much-loved “classics” which become, as such, pillaged sources of inspiration.